2013
DOI: 10.1590/s1517-86922013000100006
|View full text |Cite
|
Sign up to set email alerts
|

Caminhada/corrida ou uma partida de futebol recreacional apresentam efetividade semelhante na indução de hipotensão pós-exercício

Abstract: INTRODUÇÃO: Os exercícios aeróbios são os mais investigados e recomendados para a promoção de redução da pressão arterial. Contudo, ainda não está claro a maneira como modalidades acíclicas (voleibol, futebol e outros) podem promover hipotensão pós-exercício (HPE). OBJETIVO: Comparar a resposta pressórica aguda entre partida de futebol e uma sessão de caminhada/corrida. MÉTODOS Oito sujeitos normotensos (59,7±5 anos) e oito hipertensos (57,3±7 anos) tiveram a pressão arterial (PA) monitorada antes das sessões … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Accordingly, a prior study has reported elevated MBP in the morning compared to the evening after exercise in normotensive males [66]. In contrast, another study in healthy subjects showed no significant changes in BP after walking and running exercises [67]. Moreover, previous research did not find significant differences in HR and BP values between morning and evening after a 30 min cycling session [66].…”
Section: Physiological Parametersmentioning
confidence: 95%
“…Accordingly, a prior study has reported elevated MBP in the morning compared to the evening after exercise in normotensive males [66]. In contrast, another study in healthy subjects showed no significant changes in BP after walking and running exercises [67]. Moreover, previous research did not find significant differences in HR and BP values between morning and evening after a 30 min cycling session [66].…”
Section: Physiological Parametersmentioning
confidence: 95%
“…Accordingly, a prior study has reported elevated MBP in the morning compared to the evening after exercise in normotensive males [57]. In contrast, another study in healthy subjects showed no significant changes in BP after walking and running exercises [58]. Moreover, previous research did not found significant differences in HR and BP values between morning and evening after a 30minute cycling session [57].…”
Section: Physiological Parametersmentioning
confidence: 95%